Modified asphalt concrete as well as preparation method and application thereof

By using the method of combining modified sugarcane fibers with geological polymer aggregates, the problem of low flexural strength of geological polymer concrete is solved, the mechanical and frost resistance of modified asphalt concrete is improved, and the cost is reduced, which is suitable for temporary road removal and asphalt concrete recycling.

CN119569382AActive Publication Date: 2025-03-07HUIZHOU AUGIE WEIYE CONSTRUCTION ENGINEERING CO LTD

Patent Information

Application Number
CN202411772797.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In the prior art, geological polymer concrete has low flexural strength, high brittleness, and high cost of adding steel fibers, making it unsuitable for the demolition of temporary roads and the recycling of asphalt concrete.

Method used

Modified sugarcane fibers are combined with geological polymer aggregates, and modified sugarcane fibers are treated with acetic acid mixture and phosphorus pentoxide to improve their toughness and frost resistance. Modified asphalt is stirred and mixed with geological polymer crude aggregate and basalt fine aggregates to prepare modified asphalt concrete.

Benefits of technology

It improves the mechanical properties and frost resistance of modified asphalt concrete, reduces costs, and is suitable for the demolition of temporary roads and the recycling of asphalt concrete, which is in line with the development concept of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170655180000081
    Figure BDA0005170655180000081
  • Figure BDA0005170655180000091
    Figure BDA0005170655180000091
Patent Text Reader

Abstract

The invention discloses modified asphalt concrete and a preparation method and application thereof, and belongs to the technical field of asphalt concrete.The preparation method comprises the steps that sodium silicate, sodium hydroxide and water are stirred and mixed and then transferred into a stirring machine to serve as an alkali activator, and then fly ash, electrolytic manganese residues, cement, modified sugarcane fibers and fine sand are added into the stirring machine to be stirred and mixed; vibrating to discharge internal gas, standing, demolding and crushing to obtain geopolymer aggregate; the modified asphalt, the geopolymer coarse aggregate and the basalt fine aggregate are stirred and mixed in proportion, and the modified asphalt concrete is obtained; the geopolymer aggregate takes the electrolytic manganese residues and the fly ash as main raw materials, the utilization rate of waste resources is increased, and the modified sugarcane fibers are doped, so that the mechanical property of the geopolymer can be improved, and the application requirements of asphalt road aggregate are met. And compared with addition of steel fibers and polymer fibers, the sugarcane fibers are degradable and more environmentally friendly, and dismantling and recycling of temporary asphalt roads are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of asphalt concrete, and in particular relates to a modified asphalt concrete and a preparation method and application thereof. Background Art

[0002] Electrolytic manganese slag is waste generated in the manufacture of electrolytic manganese metal. In particular, the use of low-grade manganese ore will lead to an increase in waste. These wastes contain a large amount of heavy metal ions. Directly stacking or landfilling will cause heavy metal ions to penetrate into the soil with rainfall, causing serious environmental pollution. While vigorously developing green energy, traditional coal-fired power generation and other methods are still irreplaceable. The amount of fly ash discharged by thermal power plants is still increasing. The accumulation and treatment of a large amount of fly ash is an urgent problem to be solved.

[0003] With the development of the construction industry and the transportation industry, geopolymers are widely used in the concrete industry due to their excellent performance. Geopolymers are the product of the interaction of aluminum silicate and silicate components in an alkaline environment. They are a cement-like adhesive, in which the Al-OS i polymer structure constitutes the main component of the geopolymer structure. Electrolytic manganese slag and fly ash have complex components, including Al, Si and other elements. The prepared geopolymers can replace cement as grouting materials for application.

[0004] In the case of poor road conditions during construction, in order to ensure the smooth entry of heavy machinery and vehicles, temporary roads are generally paved first. These roads are usually demolished or restored to their original state after the construction is completed. Asphalt concrete is a pavement material with excellent performance, which is mainly composed of aggregates, asphalt and fillers. Using geopolymers as aggregates in asphalt concrete can not only recycle waste resources but also reduce construction costs, which is in line with the development concept of green environmental protection.

[0005] Geopolymers have low flexural strength and high brittleness, and need to be mixed with reinforcing fibers to improve their mechanical properties. The Chinese patent with the announcement number CN114149209B announced a steel fiber geopolymer concrete material and its performance calculation method, which improved the mechanical performance shortcomings of ordinary geopolymer concrete, such as low tensile and flexural strength, large shrinkage, and high brittleness. However, the cost of adding steel fibers is high, which is not conducive to the demolition of temporary roads and the recycling of asphalt concrete. Summary of the invention

[0006] The purpose of the present invention is to provide a modified asphalt concrete and a preparation method and application thereof.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for preparing modified asphalt concrete comprises the following steps:

[0009] Step 1: Mix sodium silicate, sodium hydroxide and water and transfer them to a mixer as an alkali activator. Then add fly ash, electrolytic manganese slag, cement, modified sugarcane fiber and fine sand into the mixer. Stir for 10-15 minutes at 200-300 r / min. Pour the slurry into a mold and vibrate on a cement vibration table for 60-100 seconds to exhaust the internal gas. Let it stand at 20-25°C for 24 hours, demold, and crush to obtain a geopolymer aggregate with a particle size of 8-12 mm.

[0010] Step 2: Mix the modified asphalt, geopolymer coarse aggregate and basalt fine aggregate with a particle size of 2-3 mm in a mass ratio of 2.5-3:10:3-5 to obtain modified asphalt concrete.

[0011] Furthermore, in step one, the mass ratio of sodium silicate, sodium hydroxide, water, fly ash, electrolytic manganese slag, cement, modified sugarcane fiber and fine sand is 2:2:100-110:200:80-85:2-3:5-8:3-5.

[0012] Furthermore, the modified asphalt in step 2 is prepared by the following steps:

[0013] The base asphalt is transferred to an oven and heated to a molten state at 160-170°C. The molten base asphalt, SBS rubber powder and nano boron nitride powder are then transferred to a high-speed shearing machine and shear mixed at 170-180°C and 4500-5000r / min for 30-40min. After shear mixing, the mixture is transferred to a high-speed mixer. Silica aerogel powder and asphalt stabilizer are added to the high-speed mixer, and stirred at 170-180°C and 1000-1200r / min for 3-3.5h to obtain modified asphalt.

[0014] Furthermore, the mass ratio of the matrix asphalt, the SBS rubber powder, the nano boron nitride powder, the silica aerogel powder and the asphalt stabilizer is 90:5-6:0.8-1.2:0.3-0.5:2-3.

[0015] Furthermore, the modified sugarcane fiber in step 1 is prepared by the following steps:

[0016] Step 1: Mix calcium chloride and zinc chloride and stir and dissolve them in an acetic acid solution with a mass fraction of 2.5% to obtain an acetic acid mixture; soak the sugarcane fiber in a sodium hydroxide solution with a mass fraction of 5% for 1.5-2 hours, then wash it with deionized water for 2-3 times and transfer it to a reactor, add the acetic acid mixture to the reactor, stir it at 200-300r / min for 1-1.5 hours, filter it, wash the retained fiber with deionized water for 2-3 times, dry it at 60-80°C to constant weight, and crush it to obtain pretreated sugarcane fiber with a length of 5-6mm;

[0017] Step 2: Add pretreated sugarcane fiber and N,N-dimethylformamide to the reactor, stir and disperse for 10-15 minutes at 20-25°C and 200-300r / min, then add phosphorus pentoxide to the reactor under the protection of nitrogen, stir continuously and heat to 120-125°C at a rate of 2-3°C / min, keep stirring for 3-3.5 hours, cool naturally, filter, wash the filter cake with deionized water and anhydrous ethanol for 3-5 times respectively, and vacuum dry to obtain modified sugarcane fiber.

[0018] Furthermore, in step 1, the dosage ratio of calcium chloride, zinc chloride and acetic acid solution is 0.4-0.8 g: 19-20 g: 100-120 mL.

[0019] Furthermore, in step 2, the dosage ratio of the pretreated sugarcane fiber, N,N-dimethylformamide and phosphorus pentoxide is 4-5 g: 180-200 mL: 1.2-1.5 g.

[0020] Beneficial effects of the present invention:

[0021] The modified asphalt concrete of the present invention uses geopolymer as coarse aggregate, and the geopolymer aggregate uses electrolytic manganese slag and fly ash as main raw materials, which improves the utilization rate of waste resources, and the modified sugarcane fiber is added therein, which can improve the mechanical properties of the geopolymer and meet the application requirements of asphalt road aggregate. Compared with adding steel fiber and polymer fiber, sugarcane fiber is degradable, more environmentally friendly, and is conducive to the demolition and recycling of temporary asphalt roads.

[0022] Soaking sugarcane fiber in sodium hydroxide solution can remove impurities such as colloids. In the acetic acid mixture, zinc chloride can swell the sugarcane fiber, causing the sugarcane fiber to expose more hydroxyl groups, promoting water, zinc ions and calcium ions to enter the gaps of the sugarcane fiber, and providing toughness to the pretreated sugarcane fiber through coordination and crosslinking between hydroxyl groups and ions on the fiber. After the modified sugarcane fiber absorbs water, zinc ions and the like can also lower its freezing point, improve the frost resistance of the modified sugarcane fiber, and thus improve the freeze-thaw splitting test strength ratio of the modified asphalt concrete.

[0023] The hydroxyl groups in the pretreated sugarcane fiber react with phosphorus pentoxide to graft a large number of phosphate groups, which helps to increase the adsorption effect of modified sugarcane fiber on heavy metals through chemical adsorption and complexation. Nano-boron nitride helps to improve the durability and stability of modified asphalt, thereby improving the antifreeze effect of modified asphalt concrete. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1: This example provides a modified asphalt concrete, which is prepared by the following method:

[0026] S1: 4 kg of calcium chloride and 190 kg of zinc chloride are mixed and then stirred and dissolved with 1000 L of 2.5% acetic acid solution to obtain an acetic acid mixture; 200 kg of sugarcane fiber is soaked in a 5% sodium hydroxide solution for 1.5 hours, then washed twice with deionized water and transferred to a reactor, the acetic acid mixture is added to the reactor, stirred at 200 r / min for 1 hour, filtered, the retained fiber is washed twice with deionized water, dried at 60° C. to constant weight, and crushed to obtain pretreated sugarcane fiber with a length of 5-6 mm.

[0027] Sugarcane fiber can be soaked in sodium hydroxide solution to remove impurities such as colloids. In the acetic acid mixture, zinc chloride can swell the sugarcane fiber, causing the sugarcane fiber to expose more hydroxyl groups, promoting water, zinc ions and calcium ions to enter the gaps of the sugarcane fiber, and providing toughness to the pretreated sugarcane fiber through coordination and cross-linking between the hydroxyl groups on the fiber and the ions.

[0028] S2: Add 40 kg of pretreated sugarcane fiber and 1800 L of N,N-dimethylformamide into the reactor, stir and disperse at 20 ° C and 200 r / min for 10 minutes, then add 12 kg of phosphorus pentoxide into the reactor under the protection of nitrogen, stir continuously and heat to 120 ° C at a rate of 2 ° C / min, keep stirring for 3 hours, cool naturally, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dry to obtain modified sugarcane fiber.

[0029] Through the reaction, the hydroxyl groups in the pretreated sugarcane fiber react with phosphorus pentoxide, and a large number of phosphate groups are grafted onto the fiber, thereby increasing the adsorption effect of the modified sugarcane fiber on heavy metals through chemical adsorption and complexation.

[0030] S3: 2kg sodium silicate, 2kg sodium hydroxide and 100kg water were stirred and mixed and then transferred to a mixer as an alkali activator. 200kg fly ash, 80kg electrolytic manganese slag, 2kg cement, 5kg modified sugarcane fiber and 3kg fine sand were added to the mixer. The mixture was stirred at 200r / min for 10min. The slurry was poured into a mold and vibrated on a cement vibration table for 60s to exhaust the internal gas. The mixture was allowed to stand at 20℃ for 24h, demolded and crushed to obtain a geopolymer aggregate with a particle size of 8-12mm.

[0031] S4: Transfer the base asphalt to an oven and heat it to a molten state at 160°C. Then transfer the molten 90kg base asphalt, 5kg SBS rubber powder and 0.8kg nano boron nitride powder to a high-speed shearing machine and shear mix them at 170°C and 4500r / min for 30min. After shear mixing, transfer the mixture to a high-speed mixer. Then add 0.3kg silica aerogel powder and 2kg asphalt stabilizer to the high-speed mixer. Stir at 170°C and 1000r / min for 3h to obtain modified asphalt.

[0032] Nano-boron nitride helps to improve the durability and stability of modified asphalt, thereby improving the antifreeze effect of modified asphalt concrete.

[0033] S5: 2.5 kg of modified asphalt, 10 kg of geopolymer coarse aggregate and 3 kg of basalt fine aggregate with a particle size of 2-3 mm were stirred and mixed to obtain modified asphalt concrete.

[0034] Example 2: This example provides a modified asphalt concrete, which is prepared by the following method:

[0035] S1: 6 kg of calcium chloride and 195 kg of zinc chloride are mixed and then stirred and dissolved with 1100 L of 2.5% acetic acid solution to obtain an acetic acid mixture; 200 kg of sugarcane fiber is soaked in a 5% sodium hydroxide solution for 1.8 hours, then washed twice with deionized water and transferred to a reactor, the acetic acid mixture is added to the reactor, stirred at 250 r / min for 1.2 hours, filtered, the retained fiber is washed twice with deionized water, dried at 70°C to constant weight, and crushed to obtain pretreated sugarcane fiber with a length of 5-6 mm.

[0036] S2: Add 45 kg of pretreated sugarcane fiber and 1900 L of N,N-dimethylformamide into the reactor, stir and disperse at 22 ° C and 250 r / min for 12 minutes, then add 13.5 kg of phosphorus pentoxide into the reactor under the protection of nitrogen, stir continuously and heat to 122 ° C at a rate of 2.5 ° C / min, keep stirring for 3.2 hours, cool naturally, filter, wash the filter cake with deionized water and anhydrous ethanol for 4 times respectively, and vacuum dry to obtain modified sugarcane fiber.

[0037] S3: 2kg sodium silicate, 2kg sodium hydroxide and 105kg water were stirred and mixed and transferred to a mixer as an alkali activator. 200kg fly ash, 82.5kg electrolytic manganese slag, 2.5kg cement, 6.5kg modified sugarcane fiber and 4kg fine sand were added to the mixer. The mixture was stirred at 250r / min for 13min. The slurry was poured into a mold and vibrated on a cement vibration table for 80s. The internal gas was discharged and allowed to stand at 22°C for 24h. The mixture was demolded and crushed to obtain a geopolymer aggregate with a particle size of 8-12mm.

[0038] S4: Transfer the base asphalt to an oven and heat it to a molten state at 160-170°C. Then transfer the molten 90kg base asphalt, 5-6kg SBS rubber powder and 0.8-1.2kg nano boron nitride powder to a high-speed shearing machine, shear and mix them at 170-180°C and 4500-5000r / min for 30-40min. After shearing and mixing, transfer the mixture to a high-speed mixer, add 0.3-0.5kg silica aerogel powder and 2-3kg asphalt stabilizer to the high-speed mixer, and stir at 170-180°C and 1000-1200r / min for 3-3.5h to obtain modified asphalt.

[0039] S5: 2.8 kg of modified asphalt, 10 kg of geopolymer coarse aggregate and 4 kg of basalt fine aggregate with a particle size of 2-3 mm were stirred and mixed to obtain modified asphalt concrete.

[0040] Example 3: This example provides a modified asphalt concrete, which is prepared by the following method:

[0041] S1: 8 kg of calcium chloride and 200 kg of zinc chloride are mixed and then stirred and dissolved with 1200 L of 2.5% acetic acid solution to obtain an acetic acid mixture; 200 kg of sugarcane fiber is soaked in a 5% sodium hydroxide solution for 2 hours, then washed with deionized water for 3 times and transferred to a reactor, the acetic acid mixture is added to the reactor, stirred at 300 r / min for 1.5 hours, filtered, the retained fiber is washed with deionized water for 3 times, dried at 80°C to constant weight, and crushed to obtain pretreated sugarcane fiber with a length of 5-6 mm.

[0042] S2: Add 50 kg of pretreated sugarcane fiber and 2000 L of N,N-dimethylformamide into the reactor, stir and disperse at 25 ° C and 300 r / min for 15 minutes, then add 15 kg of phosphorus pentoxide into the reactor under the protection of nitrogen, stir continuously and heat to 125 ° C at a rate of 3 ° C / min, keep stirring for 3.5 hours, cool naturally, filter, wash the filter cake with deionized water and anhydrous ethanol for 5 times respectively, and vacuum dry to obtain modified sugarcane fiber.

[0043] S3: 2kg sodium silicate, 2kg sodium hydroxide and 110kg water were stirred and mixed and transferred to a mixer as an alkali activator. 200kg fly ash, 85kg electrolytic manganese slag, 3kg cement, 8kg modified sugarcane fiber and 5kg fine sand were added to the mixer. The mixture was stirred at 300r / min for 15min. The slurry was poured into a mold and vibrated on a cement vibration table for 100s. The internal gas was discharged and allowed to stand at 25°C for 24h. The mixture was demolded and crushed to obtain a geopolymer aggregate with a particle size of 8-12mm.

[0044] S4: Transfer the base asphalt to an oven and heat it to a molten state at 170°C. Then transfer the molten 90kg base asphalt, 6kg SBS rubber powder and 1.2kg nano boron nitride powder to a high-speed shearing machine and shear mix them at 180°C and 5000r / min for 40min. After shear mixing, transfer the mixture to a high-speed mixer. Add 0.5kg silica aerogel powder and 3kg asphalt stabilizer to the high-speed mixer and stir at 180°C and 1200r / min for 3.5h to obtain modified asphalt.

[0045] S5: 3 kg of modified asphalt, 10 kg of geopolymer coarse aggregate and 5 kg of basalt fine aggregate with a particle size of 2-3 mm are stirred and mixed to obtain modified asphalt concrete.

[0046] Comparative Example 1: Based on Example 3, in step S1, the acetic acid mixture is not used, and the acetic acid mixture is directly replaced by acetic acid solution with a mass fraction of 2.5% to pretreat the sugarcane fiber, and the other steps remain unchanged to prepare modified asphalt concrete blue.

[0047] Comparative Example 2: Based on Example 3, the pretreated sugarcane fiber of the same mass in step S1 was directly applied to step S3 without being processed in step S2, and the other steps remained unchanged to prepare modified asphalt concrete.

[0048] Comparative Example 3: Based on Example 3, the same mass of sugarcane fiber was directly applied to step S3, and the other steps remained unchanged to prepare modified asphalt concrete blue.

[0049] Comparative Example 4: Based on Example 3, nano boron nitride powder is not added in step S4, and the other steps remain unchanged to prepare modified asphalt concrete.

[0050] The model of the matrix asphalt in the examples and comparative examples is Zhonghai 90#, and the asphalt stabilizer is purchased from Tianjin Zhongke New Materials Co., Ltd., with a model of WDJ-1.

[0051] The samples were prepared according to the corresponding standards, and the modified asphalt concrete in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for performance: the Marshall stability at 60°C (T0709-2011), elastic recovery rate at 25°C (T0662-2000) and freeze-thaw splitting test strength ratio (T0729-2000; strength after freeze-thaw cycle / strength before freeze-thaw cycle × 100%) of different samples were tested according to JTG E20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the heavy metal leaching amount of different samples, including Pb, Cd and Cr, was tested according to HJ557-2010 "Horizontal Oscillation Method for Toxicity Leaching of Solid Waste". The results are shown in Table 1:

[0052] Table 1 Modified asphalt concrete performance test table

[0053]

[0054]

[0055] As can be seen from Table 1, the comprehensive performance of the modified asphalt concrete in Examples 1 to 3 is better than that in the comparative example. Comparative Example 3 shows that the addition of modified sugarcane fiber can improve the Marshall stability, elastic recovery rate and freeze-thaw splitting test strength ratio of the modified asphalt concrete sample compared with the geopolymer aggregate prepared by adding untreated sugarcane fiber. Combined with the analysis of Comparative Example 1, it is because during the sugarcane fiber treatment process, zinc chloride can swell the sugarcane fiber, prompting the sugarcane fiber to expose more hydroxyl groups, promoting water, zinc ions and calcium ions to enter the gaps of the sugarcane fiber, and improving the toughness of the pretreated sugarcane fiber through the coordination and crosslinking between the hydroxyl groups on the fiber and the ions. Zinc ions can also improve the frost resistance of the modified sugarcane fiber, thereby improving the freeze-thaw splitting test strength ratio of the modified asphalt concrete.

[0056] Comparative Examples 1 to 3 show that after treatment with phosphorus pentoxide, the hydroxyl groups in the pretreated sugarcane fibers are reacted and grafted with phosphate groups, which can improve the adsorption effect of the modified sugarcane fibers on heavy metals in geopolymer raw materials. Comparative Example 4 shows that nano-boron nitride can synergistically improve the antifreeze effect of modified asphalt concrete.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing modified asphalt concrete, characterized in that: The steps include: Step 1: Mix sodium silicate, sodium hydroxide and water and transfer them to a mixer as an alkali activator. Then add fly ash, electrolytic manganese slag, cement, modified sugarcane fiber and fine sand into the mixer, stir for 10-15 minutes at 200-300r / min, pour the slurry into a mold and vibrate on a cement vibration table for 60-100s, stand at 20-25℃ for 24h, demould, and crush to obtain a geopolymer aggregate with a particle size of 8-12mm; Step 2: Mix the modified asphalt, geopolymer coarse aggregate and basalt fine aggregate with a particle size of 2-3 mm in a mass ratio of 2.5-3:10:3-5 to obtain modified asphalt concrete.

2. The method for preparing modified asphalt concrete according to claim 1, characterized in that: The mass ratio of sodium silicate, sodium hydroxide, water, fly ash, electrolytic manganese slag, cement, modified sugarcane fiber and fine sand in step 1 is 2:2:100-110:200:80-85:2-3:5-8:3-5.

3. The method for preparing modified asphalt concrete according to claim 1, characterized in that: The modified sugarcane fiber obtained in step 1 is prepared by the following steps: Add pretreated sugarcane fiber and N,N-dimethylformamide into the reactor, stir and disperse at 20-25°C and 200-300r / min for 10-15min, add phosphorus pentoxide into the reactor under the protection of nitrogen, stir continuously and heat to 120-125°C at a rate of 2-3°C / min, keep stirring for 3-3.5h, cool naturally, filter, wash the filter cake with deionized water and anhydrous ethanol for 3-5 times respectively, and vacuum dry to obtain modified sugarcane fiber.

4. The method for preparing modified asphalt concrete according to claim 3, characterized in that: The dosage ratio of the pretreated sugarcane fiber, N,N-dimethylformamide and phosphorus pentoxide is 4-5g:180-200mL:1.2-1.5g.

5. The method for preparing modified asphalt concrete according to claim 3, characterized in that: The pretreated sugarcane fiber is prepared by the following steps: The sugarcane fiber is soaked in a 5wt% sodium hydroxide solution for 1.5-2h, washed and transferred to a reactor, calcium chloride and zinc chloride are mixed and dissolved with a 2.5wt% acetic acid solution, and the acetic acid mixture is added to the reactor, stirred at 200-300r / min for 1-1.5h, filtered, and the retained fiber is washed with deionized water for 2-3 times, dried at 60-80°C to constant weight, and crushed to obtain pretreated sugarcane fiber with a length of 5-6mm.

6. The method for preparing modified asphalt concrete according to claim 5, characterized in that: The dosage ratio of the calcium chloride, zinc chloride and acetic acid solution is 0.4-0.8 g: 19-20 g: 100-120 mL.

7. The method for preparing modified asphalt concrete according to claim 1, characterized in that: The modified asphalt described in step 2 is prepared by the following steps: Heat the base asphalt at 160-170°C to a molten state, then transfer the molten base asphalt, SBS rubber powder and nano boron nitride powder to a high-speed shearing machine, shear and mix at 170-180°C and 4500-5000r / min for 30-40min, transfer the mixture to a high-speed mixer and add silica aerogel powder and asphalt stabilizer, stir at 170-180°C and 1000-1200r / min for 3-3.5h to obtain modified asphalt.

8. The method for preparing modified asphalt concrete according to claim 7, characterized in that: The mass ratio of the matrix asphalt, SBS rubber powder, nano boron nitride powder, silicon dioxide aerogel powder and asphalt stabilizer is 90:5-6:0.8-1.2:0.3-0.5:2-3.

9. A modified asphalt concrete, characterized in that: The modified asphalt concrete is prepared by the preparation method of any one of claims 1 to 8.

10. Use of the modified asphalt concrete according to claim 9 in temporary asphalt roads.

Citation Information

Patent Citations

  • Corn straw fiber enhanced fly ash polymer gel material and preparation method thereof

    CN104108903A

  • Carboxymethylated and phosphorylated bamboo fibers as well as preparation method and application thereof

    CN109046263A

  • Abradable seal coating material and preparation method thereof

    CN114085612A

  • Method for rapidly repairing road cracks based on geopolymer modified asphalt

    CN116607365A

Cited By

  • Environment-friendly high-strength asphalt concrete and preparation method thereof

    CN120058280A

  • Recycled asphalt concrete and preparation method thereof

    CN120328918A